Improving Quality of Life and HIV Prevention in Productive Age with Vesta Indonesia Foundation in Umbulharjo - Hepi, Buana; Br Ginting, Stepany Melani; Ferella; M. Rizky; Harahap, Muhammad Rizqi fadhil; Megy Patricia Ilato (Yayasan Putra Adi Dharma, 2024)
HIV (Human Immunodeficiency Virus) is a type of virus that causes the body's immune system to malfunction. AIDS, also known as Acute Immune Deficiency Syndrome, is a group of diseases that develop as a result of HIV infection in the body. Injecting drug use, Promiscuous sex, especially sex with the same sex, Through blood transfusion From mother to child, Oral sex. HIV transmission can be prevented by being faithful to one's partner, avoiding multiple partners, avoiding drug use especially through needles and proper HIV education on transmission, prevention and treatment can help prevent HIV transmission in the community. Yayasan Vesta Indonesia is a group of volunteers who conduct health education on sexual and reproductive health issues in the Special Region of Yogyakarta.